Magnetic properties of bulk, and rapidly solidified nanostructured (Nd1-xCex)2Fe14-yCoyB ribbons. (15th January 2016) - Pathak, Arjun K.; Khan, M.; Gschneidner, K.A.; McCallum, R.W.; Zhou, L.; Sun, K.; Kramer, M.J.; Pecharsky, V.K.
Abstract: Magnetic properties of Ce and Co co-doped (Nd1-x Cex )2 Fe14-y Coy B compounds have been investigated both in bulk polycrystalline and rapidly solidified nanostructured ribbon forms. For certain Ce concentrations the materials exhibit spin re-orientation transitions below 140 K. The Curie temperatures, saturation magnetizations, and other magnetic properties relevant for applications as permanent magnets are controlled by Ce and Co substitutions for Nd and Fe, respectively. Most importantly, the results show that Ce, Co co-doped compounds are excellent replacements for several Dy-based high performance permanent magnets (dysprosium is one of the critical elements and is, therefore, in short supply). The high temperature (>375 K) magnetic properties for Nd–Ce–Fe–Co–B based alloys show promise not only as a replacement for Dy-doped Nd2 Fe14 B permanent magnets, but the new alloys also require significantly lower amounts of Nd, which too is the critical element that can be replaced by a more abundant Ce. Graphical abstract: Transmission electron microscopy (TEM) micrographs of the free side (a), the wheel side (b) of (Nd0.8 Ce0.2 )2 Fe14 B melt spun ribbon. (c) Maximum energy product, (BH)max, as functions of temperature for melt spun ribbons of Nd2 Fe14 B, (Nd0.8 Ce0.2 )2 Fe14 B and (Nd0.8 Ce0.2 )2 Fe14 Co2 B.